Function and Role of Internal Audit. Comparative Study Based On the Process, Report and Value Added of the Audit - Bekteshi, Jonida (UNWE Yearbook, 2023)
Internal audit protects the organization from potential risks and damage to reputation, financial operations, fraud and non-compliance with the legal and regulatory framework. The objectivity, independence, and broad perspective that internal auditors have throughout the organization make internal auditors very useful to management and the board of directors. Internal audit has emerged as one of the organizational areas that should have a complete assessment tool, oriented not only towards finding business errors, but towards improving business performance. Around the 20th century, the creation of a formal internal audit function, whose responsibilities could be delegated, was seen as the most logical answer. An important aspect of the history of audit theory is the role and functions of auditors. Auditing is an important business function that involves evaluating evidence and documentation related to an organization's economic activities and transactions.
Keywords: Internal audit; Function; Role; Report; Value added